Probiotics and Paraprobiotics—New Proposal for Functional Food - Barbara Sionek; Magdalena Gantner (Applied Sciences)
The interest in functional food products offering health benefits for consumers is constantly growing. The functional food products available on the market supplied with probiotics also contain paraprobiotics, postbiotics, and prebiotics, which act synergistically. Recently, more attention has been paid to non-viable bioactive food components. Paraprobiotic’s pro-health effects are similar to those of probiotics, including, among others, anti-inflammatory, immunomodulatory, antiproliferative, antioxidant and antibacterial activities. As non-viable microorganisms, paraprobiotics have a better safety profile than probiotics. The safety profile favors them for usage in vulnerable people; however, their effectiveness should be proven in clinical trials. Paraprobiotics do not carry the risk of antibiotic resistance, transfer, or acquisition. The effect of paraprobiotics is strain-dependent and related to the method of inactivation. Paraprobiotics seem to be neutral in various food matrices, and their usage is convenient regardless of physicochemical stress. They have little or no impact on the product’s sensory traits and quality. Their addition can extend the shelf life and reduce the risk of food contamination. These advantages of paraprobiotics create great possibilities for the development of the food industry. However, the lack of separate regulations for non-viable microorganisms appears to be the main obstacle for this segment of food manufacturing.